Pengaruh Lingkungan Internal dan Eksternal terhadap Kinerja Industri Kecil Keramik Dinoyo Kota Malang - Pudjihardjo, H. M.; Kurniawati, Desi Tri (Jurnal Aplikasi Manajemen, 2011)
The research is aimed to analyze effect of environment variable both in internal environment (marketing, financial and production), or external environment (buyer, competitor, technology, government) simultaneously and partial good also the dominant variable toward performance of small and medium enterprises ceramics at Dinoyo, Malang. The result research has some suggestions, such as improvement with increasing ceramic industry of Dinoyo, Malang: (1) In increasing development for industry of ceramic Dinoyo, Malang, the local government, especially industry and commercial department office should do education by giving training, controlling and quality control product, and also education in financial area, such, financial, marketing, and management, (2) Production is one of important factor necessary for craftsman in order to be more sensitive to develop their product in good quality. Another important factor is marketing, financial, and technology. (3) The craftsman should be more increasing of company performance, so it can maximize product result desired in increasing quality product. (4) Service quality to customer must be increased, so the customer likes and interest in buying ceramic product. The craftsman should be more opened in receiving criticism from their customers. (5) The future research can continue and improve this research on more adequate and more deepening research indicator or entering other variable not discussed yet on this research.